2015
DOI: 10.4103/1735-3327.161462
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal changes following molar intrusion with miniscrews

Abstract: Background:With the introduction of skeletal anchorage system, recently it is possible to successfully intrude molar teeth. On the other hand, there have been concerns about periodontal changes associated with intrusion and there are few studies on this topic, especially for posterior teeth.Materials and Methods:Ten female patients were enrolled in this study. Maxillary molar intrusion was achieved by inserting two miniscrews and a 17 × 25 titanium molybdenum alloy spring. Crestal height changes were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
(62 reference statements)
3
9
0
1
Order By: Relevance
“…Both studies assessed different biological side effects of intrusion. Ma Dan et al 17 reported no significant difference in probing depth and width of the keratinized gingiva between the TAD and utility arch groups, this is in agreement with Bayani et al 27 that found no significant change of probing depth during intrusion with miniscrew. In fact, a clinical attachment gain and shortening of clinical crown height has been observed.…”
Section: Dovepresssupporting
confidence: 71%
“…Both studies assessed different biological side effects of intrusion. Ma Dan et al 17 reported no significant difference in probing depth and width of the keratinized gingiva between the TAD and utility arch groups, this is in agreement with Bayani et al 27 that found no significant change of probing depth during intrusion with miniscrew. In fact, a clinical attachment gain and shortening of clinical crown height has been observed.…”
Section: Dovepresssupporting
confidence: 71%
“…9 In a study conducted by Bayani S, et al in 2015, they stated that the maxillary molar intrusion treatment with miniscrew showed no significant probing depth throughout the treatment. 10 However the Ghanbari, et al study showed that periodontal health was affected by the miniscrews as the plaque accumulation increased. 11 Inadequate personal oral hygiene is known as one of the major risk factors for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In our molar intrusion case, the alveolar bone and the gingiva did not follow the tooth movement. Few reports are available on clinical periodontal changes after molar intrusion, 12 , 18 , 20 including histological findings from animal experiments. 15 , 16 , 19 , 22 According to Kanzaki et al, 16 during molar intrusion with skeletal anchorage devices, pressure from supra-alveolar fibers induces alveolar bone resorption and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…4 - 11 The mean amount of molar intrusion with TADs has been clarified and ranges from 2.1 mm to 4 mm. 4 - 6 , 10 , 12 , 13 For extreme supra-erupted second molars, intrusion can reach 8 mm. 14…”
Section: Introductionmentioning
confidence: 99%